Clinicopathological and prognostic significance of LINC00673 in human malignancy: a review and meta-analysis. Issue 7 (30th July 2021) - Zhu, Yurong; Zhang, Zhifa; Peng, Hui; Li, Weiping; Hu, Shaowei; Zhao, Min; Lin, Weifeng
Abstract: Background: We conducted this research to investigate the relationship between long intergenic non-protein coding RNA 673 (linc00673) expression and prognosis and clinicopathological parameters in human malignancies. Methods: The PubMed, Embase, WOS, and CNKI databases were used to collect eligible research data before 4 January 2021. Meta-analysis was performed using Stata 12.0 software. Pooled odds ratios (ORs) or hazard ratios (HRs) and their 95% confidence interval (CIs) were calculated to evaluate the association of linc00673 expression with survival outcomes and clinical parameters. Results: We finally included 17 articles and a total of 1539 cases for the meta-analysis. The results indicated that linc00673 was significantly correlated with T stage ( P =0.006), tumor stage ( P <0.001), lymph node metastasis ( P <0.001), and distant metastasis ( P <0.001). In addition, the results suggested that elevated linc00673 expression predicted a poor overall survival (OS) time ( P =0.013) and acted as an independent prognostic factor ( P <0.001) for OS in patients with malignancy. Although potential evidence of publication bias was found in the studies on OS in relation to tumor stage in the multivariate analysis, the trim-and-fill analysis confirmed that the results remained stable. Conclusions: Overexpression of linc00673 was significantly correlated with shorter OS time in patients with malignant tumors. Moreover, the increased expression level of linc00673 was significantly correlated with T stage, tumor stage, lymph node metastasis, and distant metastasis. The results presented in this article revealed that linc00673 might be involved in the progression and invasion of malignancy and serve as a novel prognostic biomarker and potential therapeutic target for malignancy.